República de Platón a través de Marías: la construcción de un Estado justo que no asegura la felicidad individual - Zúñiga Acurio, Luis Sebastián (2022)
In The Republic, Plato attempts to define justice, for which he draws an analogy between man and the State; in this comparison happiness is seldomly mentioned. Happiness of the individual is affected by Plato’s conception, as this is collective and communal in nature, resulting in Plato’s interest to search for the happiness of the State, rather than of a group. Even if this ideal city model fosters economic development, great asymmetry between classes persists in the State, preventing many of its citizens from achieving their expectations. This work deals with Julian Marias’ perspective on happiness, which alludes to the fulfilment of wishes and desires of individuals; and when this is not achieved, discontent arises. In Plato’s city, due to the differences between the lifestyles of the three classes, the surge of discontent is unavoidable.